1993
DOI: 10.1093/cvr/27.12.2186
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmic effects of the class III agent almokalant: importance of infusion rate, QT dispersion, and early afterdepolarisations

Abstract: The rate of infusion of repolarisation delaying agents may influence the dispersion of repolarisation and play a decisive role in the initiation of torsade de pointes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(126 citation statements)
references
References 0 publications
8
114
0
4
Order By: Relevance
“…5,6 "Proarrhythmic" compounds were selected from compounds with a TdP incidence Ͼ60%. "Less proarrhythmic compounds" were selected from compounds with a TdP incidence Յ25 (Table I).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 "Proarrhythmic" compounds were selected from compounds with a TdP incidence Ͼ60%. "Less proarrhythmic compounds" were selected from compounds with a TdP incidence Յ25 (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Ten minutes later, the compound under investigation was infused for 30 minutes; 5 minutes later, the dose was increased up to 10-fold. The first dose lengthened the guinea pig monophasic APD by 20% (Table I).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…azimilide (Jiang et al, 1999) and almokalant (Carmeliet, 1993). However, almokalant, which is a selective IK r -inhibiting compound, has the potential to induce TdP in the methoxamine-sensitised rabbit model and in man (Carlsson et al, 1993a;Darpö et al, 1996). Hence, the prepulse potentiation of hERG can not by itself explain the low proarrhythmic potential of AZD7009 but may contribute when combined with other protective properties.…”
Section: Mechanisms Underlying the Low Proarrhythmic Potential Of Azdmentioning
confidence: 99%
“…Verduyn et al, 1997;Hohnloser, 1997 . It was demonstrated that almokalant, a selective I blocker, signifiKr cantly reduced the incidence of coronary artery occlusionr reperfusion-induced arrhythmias but also showed marked Ž proarrhythmic activity Carlsson et al, 1993a;Farkas et . al., 1998 .…”
Section: Discussionmentioning
confidence: 99%